EMPOWERING ARTISANS THROUGH INNOVATIVE EDUCATIONAL MEDIA PRODUCTS MADE FROM WOOD WASTE AT KAMPOENG SEMBADA UKIR PETEKEYAN, JEPARA, CENTRAL JAVA - Putri Purwaningrum, Jayanti; Andriani, Evana; Fajrie, Nur; Widagdo, Jati (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Kampoeng Sembada Ukir Petekeyan is located in Petekeyan Village, Tahunan District, Jepara Regency, Central Java . Most of the people in Petekeyan Village make a living as craftsmen in the furniture/carving furniture industry. The handicraft commodities are interior products (cabinets, dining chairs, guest chairs, etc.) and exterior products (garden chairs, patio chairs). The cultural identity of the handicraft-producing community is inherited by the process of enculturation of soft skills. Currently, the management of wood waste from the furniture industry has not been optimal. The problem experienced by partners is the unplanned disposal of industrial waste making the slum environment and some supporting facilities and infrastructure less functional, such as the disposal of wood waste on the shoulder of the road and drainage channels that clog the flow of water so that it overflows into the road and the road section becomes damaged. Thus, there is a need for effective wood waste management so that settlements become healthy and livable. The methods used in service at woodworkers are socialization and training, discussions and workshops. The results of this activity are 1) knowledge of wood craftsmen in wood waste management has increased and 2) partners have skills and experience in making innovative educational media products made from wood waste that are of economic value.